Young people as a subject of human resources management in the third sector organizations = Młodzi ludzie jako podmiot zarządzania zasobami ludzkimi w organizacjach trzeciego sektora - Stankiewicz, Janina; Seiler, Bartosz; Bortnowska, Hanna (Zielona Góra: Faculty of Economics and Management Press)
In democratic societies, citizens join as volunteers in the management of various areas of the social sphere. They do this by engaging in non-profit organizations` activities. People are the basis for the functioning of these entities, so it is possible to use appropriately adapted HRM methods and tools. The important part of the social workforce of non-profit organizations is young people (up to the age -of 26).
Keywords: trzeci sektor; ludzie młodzi; zaangażowanie; zarządzanie zasobami ludzkimi; third sector; young people; commitment; human resources management (HRM)